A Philosophical Comparative Study of the Concept of Brahman (God) in Advaita Vedanta and the Coexistential Philosophy of A. Nagraj (1990) - Chhanwal, Sunil (International Journal of Advanced Research in Peace, Harmony and Education; Vol 10 No 1 (2025): International Journal of Advance Research in Peace, Harmony and Education, 2025)
This paper presents a comparative philosophical study between the Concept of God (Brahman) in Vedanta (Advet) and Co-existential Philosophy by A. Nagraj. These two Philosophy, address the nature of reality, self, and existence. Advaita Vedanta, rooted in the ancient Indian spiritual tradition, posits a non-dualistic metaphysics in which Brahman alone is real, and the world is an illusory projection, known as Maya. Liberation is achieved through self-realization, wherein the individual self (Atman) is understood as identical to Brahman. In contrast, Coexistential Philosophy, a contemporary Indian framework developed by A. Nagraj, affirms the co-existence of the immaterial, inactive Brahman (Kriyashunya) and the active, material world (Kriyasheel). It offers a holistic and practical approach that emphasizes harmony among humans, society, and nature. Unlike Advaita, it upholds the reality and significance of the material world and proposes a human-centric realization through direct experience and ethical living. The study highlights their ontological, epistemological, and ethical distinctions while suggesting that both philosophies offer complementary insights—Advaita through transcendence and inner realization, and Coexistential Philosophy through engagement and harmonious living.